Analysis of Economic Growth At Poverty Level With Meta-Analysis - Hidayat, Nurul; Ilahi, Lailiy Kurnia; Najiatun, Najiatun; Arifah, Hertin Khalifatun Nisa (MediaTrend, 2024)
This study aims to determine the impact of economic growth on the poverty rate by meta-analysis using Stata 15.0 software. The number of observations used was 41 research articles in Indonesia which examined the relationship between economic growth and poverty levels. In general, the results of his research show a negative effect with a parameter coefficient value of -0.170 percent . This is influenced by the type of data and the number of observations that have a significant effect. In variable data types, if the data used is panel data it produces a stronger negative relationship than using time series or cross section data types . In the number of observations variable, the more the number of observations (N) used tends to produce a positive coefficient value, research that produces a negative coefficient value occurs in certain cases regarding the relationship of economic growth to the poverty level. Of the 41 research articles analyzed through the meta funnel plot of the standard error coefficient , it is known that there is publication bias, as seen from the study with a small sample size that is not symmetrically distributed.